The family Carabodidae (Acari: Oribatida) V. The genus Congocepheus (first part) with redescriptions of Congocepheus heterotrichus Balogh 1958, Congocepheus orientalis Mahunka 1987 and Congocepheus hauseri Mahunka 1989 - Fernandez, Nestor Alfredo (2014)
Congocepheus heterotrichus Balogh 1958, Congocepheus orientalis Mahunka 1987 and Congocepheus hauseri Mahunka 1989 are redescribed and illustrated based on adult specimens, using optical microscopy. Detailed descriptions are given of the three species, but detailed leg studies are available only for specimens of C.orientalis and C.hauseri. Several errors in the original descriptions are addressed.